2020
DOI: 10.1038/s41598-020-71771-8
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation as a tool to tune antimicrobial activity of peptoids

Abstract: Antimicrobial peptides have attracted considerable interest as potential new class of antibiotics against multi-drug resistant bacteria. However, their therapeutic potential is limited, in part due to susceptibility towards enzymatic degradation and low bioavailability. Peptoids (oligomers of N-substituted glycines) demonstrate proteolytic stability and better bioavailability than corresponding peptides while in many cases retaining antibacterial activity. In this study, we synthesized a library of 36 peptoids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 46 publications
3
65
1
Order By: Relevance
“…For example, while MXB-9 exhibits potent antiviral activity, its structural analog MXB-10 has no effects on viral propagation. This difference in activity potentially can be explained by differences in net molecular hydrophobicity upon halogen substitution as previously reported by Molchanova et al [34]. In this study they found an increasing antimicrobial activity correlating with increasing hydrophobicity, until a threshold was reached where the activity dropped.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For example, while MXB-9 exhibits potent antiviral activity, its structural analog MXB-10 has no effects on viral propagation. This difference in activity potentially can be explained by differences in net molecular hydrophobicity upon halogen substitution as previously reported by Molchanova et al [34]. In this study they found an increasing antimicrobial activity correlating with increasing hydrophobicity, until a threshold was reached where the activity dropped.…”
Section: Discussionsupporting
confidence: 83%
“…Given the partial success of MXB-1 and MXB-5, a further library of compounds was developed by hybridizing the key features of these compounds. The activity and potency of these cationic, amphipathic peptoids was found to be affected by their self-assembly into stable, ellipsoidal micelles or other structures (unpublished results; and [ 34 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fluorine substituted peptoids had enhanced antimicrobial activity against both Gram-(+) and Gram-(-) bacteria without toxicity to mammalian cells [ 216 ]. Recently, a study on the effect of the halogenation in α-peptoids investigated the relationship between the nature of the halogen and the degree of halogenation, their ability to self-assemble into nanostructures and their antimicrobial activity [ 217 ]. Sets of scaffolds of four sizes were used containing alternating NLys and NPhe units, where F, Cl, Br and I atoms were introduced into position 4 of the phenyl rings.…”
Section: Halogenated Ampsmentioning
confidence: 99%
“…255 Furthermore, the group was able to establish a correlation between the biological effect of the halogenation and the relative hydrophobicity of the compounds, as well as their self-assembly properties. 256 The lipophilicity of peptoid oligomers greatly affects antimicrobial activity. By screening a peptoid library against several bacterial strains using a peptoid library agar diffusion (PLAD) assay, Turkett and Bicker established a basis for future designs of peptoid libraries.…”
Section: Peptoids and Peptoid-hybrids With Antimicrobial Activitymentioning
confidence: 99%